Time Course of Performance Indexes, Oxidative Stress, Inflammation, and Muscle Damage Markers after a Female Futsal Match - Athanasios Souglis; Dimitrios I. Bourdas; Aristotelis Gioldasis; Ioannis Ispirlidis; Anastassios Philippou; Emmanouil Zacharakis; Alexandros Apostolidis; Georgios Efthymiou; Antonios K. Travlos (MDPI AG, 2023)
Background: Our aims were to investigate the time-course effects of a futsal match on performance, oxidative stress, and muscle damage markers, as well as inflammatory and antioxidant responses during a 6-day post-match period. Methods: Thirty-four female high-level futsal players were assessed on several oxidative stress, inflammation, subjective muscle soreness, subjective rate perceived exertion, and performance tests before a futsal match, immediately after, and 24 h to 144 h after. Results: Counter movement jump, 20 m, and 10 m sprints performance significantly decreased immediately after the match (p < 0.05) and returned to baseline 72 h post-match (p > 0.05). Delayed onset muscle soreness peaked 24 h post-match and rate perceived exertion peaked post-match (p < 0.05) and returned to baseline 96 h post-match (p > 0.05). Inflammatory biomarkers peaked at 24 h (p < 0.05) and remained significantly elevated for 72 h after the match (p < 0.05). Muscle damage biomarkers peaked at 24 h (p < 0.05) and remained significantly (p < 0.05) elevated for at least 72 h after the match. Oxidative stress markers peaked at 24 h-48 h (p < 0.05) and returned to baseline 120 h post-match (p > 0.05). In respect to antioxidant responses, these peaked at 24 h-48 h post-match (p < 0.05) and returned to baseline 120 h after the match (p > 0.05). Conclusions: A single futsal match induces short/mid-term changes in performance, inflammation, oxidative stress, and muscle damage markers for about 72 h-96 h post-match.